EXPERIMENTAL-DETERMINATION OF MN-MG MIXING PROPERTIES IN GARNET, OLIVINE AND OXIDE - Wood, B; Hackler, R; Dobson, D (Springer-Verlag, 1994)
We have measured the mixing properties of Mn-Mg olivine and Mn-Mg garnet at 1300° C from a combination of interphase partitioning experiments involving these phases, Pt-Mn alloys and Mn-Mg oxide solid solutions. Activity coefficients of Mn dilute in Pt-Mn alloys at 1300° C/1 atm were measured by equilibrating the alloy with MnO at known fO2. Assuming that the log fO2 of the Mn-MnO equilibrium under these conditions is-17.80 (Robie et al. 1978), we obtain for γMn: logγMn = -5.25 + 3.67 XMn + 11.41X2Mn Mixing properties of (Mn,Mg)O were determined by reversing the Mn contents of the alloys in equilibrium with oxide at known fO2. Additional constraints were obtained by measuring the maximum extent of immiscibility in (Mn,Mg)O at 800 and 750° C. The data are adequately described by an asymmetric (Mn,Mg)O solution with the following upper and lower limits on nonideality: (a) WMn = 19.9kj/Mol; WMg = 13.7kj/Mol; (b) WMn = 19.9kj/Mol; WMg = 8.2kj/Mol; Olivine-oxide partitioning was tightly bracketed at 1300° C and oxide properties used to obtain activity-composition relations for Mn-Mg olivine. Despite strong M2 ordering of Mn in olivine, the macroscopic properties are adequately described by a symmetric model with: Wol = 5.5 ± 2.5 kj/mol (1-site basis) Using these values for olivine, garnet-olivine partitioning at 27 kbar/1300° C leads to an Mn-Mg interaction parameter in garnet given by: Wgt = 1.5 ± 2.5kJ/mol (1-site basis) Garnet-olivine partitioning at 9 kbar/1000° C is consistent with the same extent of garnet nonideality and the apparent absence of excess volume on the pyrope-spessartine join indicates that any pressure-dependence of WGt must be small. If olivine and garnet properties are both treated as unknown and the garnet-olivine partitioning data alone used to derive WOl and WGt, by multiple linear regression, best-fit values of 6.16 and 1.44 kJ/mol. are obtained. These are in excellent agreement with the values derived from metal-oxide, oxide-olivine and olivine-garnet equilibria. © 1994 Springer-Verlag.